Evaluating the sustainability and long-term outcomes of the Home Care Support Intervention Program (HoSIP) to reduce loneliness among community-dwelling older adults: A two-year follow-up study - Elham Lotfalinezhad; Shannon Freeman; Ahmad Kousha; Karen Andersen-Ranberg; Jeffrey E. Stokes; Sama Amirkhani-Ardeh; Ahmad Sohrabi; Farzaneh Barati; Mina Hashemiparast; Mohammad Asghari-Jafarabadi; Mohammad Reza Honarvar; Haidar Nadrian (PLoS ONE, 2025)
Introduction Understanding the long-term effects of home care support programs on loneliness in older adults is crucial for optimizing service delivery and improving the quality of life and care. This research explores the Sustainability and Long-Term Outcomes of the Home Care Support Intervention Program (HoSIP) to Reduce Loneliness among Community-dwelling Older Adults: A two-year follow-up study. Method and materials This concurrent nested mixed-method study investigated the impact of HoSIP on older adults two years post-implementation. Quantitative data were collected on loneliness, social networks, perceived social support, quality of life, self-care ability, and general health. RAMNOVA analysis was used to analyze the results of univariate tests conducted at different points of measurement using SPSS version 23. Sixteen participants completed semi-structured individual interviews in-person and virtually. Conventional content analysis was undertaken using MAXQDA version 20. Results Sixteen older adults remained in the HoSIP program at the two-year post-test assessment (mean age 73.5 years + 6.6 years). The participants were predominantly female (81.3%). Over two years compared to baseline, a significant decline was observed in loneliness, social network, perceived social support, quality of life, self-care ability ( p < 0.05) while no significant changes were observed for general health ( p > 0.05). Three main categories, along with forth sub-categories, emerged from the data analysis. Discussion This study explored how a community-based program helped reduce loneliness in older adults. The results highlight the importance of involving older adults in designing programs to improve their overall well-being. These findings can guide future interventions to enhance the quality of life for older adults, potentially lowering healthcare costs and benefiting both individuals and governments. This program provides a framework for the development and implementation of sustained, community-based interventions directed by older adults. Given the potential impacts of sociocultural factors on the efficacy and longevity of such programs, these elements warrant careful consideration during the design phase of the similar interventions.